(untitled) - Griffith, Robert E.; Chakiris, George; Bernstein, Leonard; 1918-1990; Leven, Boris; Prince, Harold; 1928-2019; Laurents, Arthur; Moreno, Rita; 1939-; Lehman, Ernest; 1915-2005; et al. (MGM Home Entertainment, 2003)
This musical sets the tragedy of Romeo and Juliet against a backdrop of the rivalry of two street gangs, the Sharks and the Jets, in New York of the 1950s. A young woman who is sister to the Sharks leader has her first taste of love with the former head of the Jets.
Keywords: Drama; First loves; Drama; New York (State); Gangs; Based on the book; Video recordings for the hearing impaired; Musical films; Feature films